PENGARUH KARAKTERISTIK EKSEKUTIF TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY : AGRESIVITAS PAJAK SEBAGAI VARIABEL INTERVENING - Nur Istriasih; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
This study aims to examine the influence of characteristics risk-taking executive with corporate social responsibility (CSR) disclosure through tax aggressiveness as an intervening variable. The population of this study was non-financial companies listed in Indonesia Stock Exchange (ISX) in 2012-2013.There are three results of this study. First result of this study showed that the characteristics risk taker executive significantly and positive related to aggressiveness of corporate taxes. A company that has a risk-taking executives have a greater possibility to commit acts of tax aggressiveness than a company which has a risk-averse executive. Second, this study showed that tax aggressiveness significantly and negative related to CSR disclosure. Companies that have a low level of tax aggressiveness resulting company would disclose CSR greater than the firm that does tax aggressiveness. And third result showed that tax aggressiveness can’t mediate the relationship of characteristics executive to CSR disclosure.